Oceanography and Marine Biology An annual review. Volume 61 - Hawkins, S. J.; Todd, P. A.; Russell, B. D.; Lemasson, A. J.; Allcock, A. L.; Byrne, M.; Firth, L. B.; Lucas, C. H.; Marzinelli, E. M.; Mumby, P. J.; Sharples, J.; Smith, I. P.; et al. (Taylor & Francis, 2023)
Oceanography and Marine Biology: An Annual Review remains one of the most cited sources in marine science. The increasing interest in oceanography and marine biology and its relevance to global environmental issues, especially global climate change and its impacts, creates a demand for authoritative refereed reviews summarising and synthesising the results of both historical and recent research. For more than 50 years, OMBAR has been an essential reference for researchers, students and workers in all fields of marine science. An international Editorial Board ensures global relevance and expert peer review, with editors from Australia, Hong Kong, Ireland, Singapore, and the UK. The series of volumes can be found in the libraries of institutes and universities worldwide. Five of the seven peer-reviewed contributions in Volume 61 are available to read Open Access via this webpage and on OAPEN. Supplementary material is provided online on the Support Materials tab on the book's www.routledge.com webpage for Reviews 1, 2, 4, 5 and 6. Volume 61 features a review of 100 years of daily sea surface temperature from the Hopkins Marine Station in Pacific Grove, California; an exploration of the biology and life cycle of enigmatic crustacean y-larvae; a review of the science, policy and management of the Central and South Atlantic Deep-Sea benthos; a review of the biodiversity of the Irish-Scottish continental margin; an investigation of how new molecular tools can be used for marine biodiversity and ecosystem assessments, and a look at the resilience of marine organisms to climate change. A final monograph considers enemy shells as refugia from grazing and competition pressure. If you are interested in submitting a review for consideration for publication in OMBAR, please email the new co-Editors in Chief, Dr Peter Todd (dbspat@nus.edu.sg) and Dr Bayden Russell (brussell@hku.hk). Guidelines for contributors to OMBAR, including information on illustration requirements, can be downloaded on the "Support Material" tab on the latest volume's webpage.